Neurotrophic Keratitis. Etiology, Pathogenesis, Clinical Manifestations. Review. Part 1 - E. A. Kasparova; N. R. Marchenko (Oftalʹmologiâ)
Neurotrophic keratitis (also called neurotrophic keratopathy) (NTK) is a degenerative disease of the cornea, accompanied with neurogenic inflammation. It caused by a sensitive innervation loss of the trigeminal nerve and characterized by reduced sensitivity of the cornea and a retardation of its healing process. NTC-causing damage to the trigeminal nerve can occur at different levels-from the nucleus to the terminals located in the cornea, and can be caused by ocular and systemic diseases both. The most common causes include herpetic keratitis, diabetes, chemical burns and iatrogenic injuries during ophthalmic operations, intracranial neoplasms, disorders of cerebral circulation and neurosurgical interventions. Corneal changes include epitheliopathy (grade I), persistent erosion (grade II), ulcer and its complications (grade III). The determining diagnostic sign of NTK is a decrease or loss of corneal sensitivity. The morphological characteristics of the corneal nerves can be studied using confocal microscopy.